Status and Challenges of Anti-Bullying Implementation Program in the School - Beler, Flora Kris E.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study aimed to examine the status and challenges of the anti-bullying program implementation at Labuan Central School, Zamboanga City, for the academic year 2024–2025. Specifically, it assessed the extent of policy implementation, the effectiveness of incident reporting and response systems, and the level of teacher awareness and participation. The research employed a descriptive-correlational design, using survey questionnaires administered to 76 randomly selected teachers from the total population of 95. Results revealed that while the school demonstrated high compliance with anti-bullying policies and teacher awareness was generally strong, challenges persisted in the areas of consistent enforcement, functionality of reporting systems, and adequacy of training and resources. Notably, statistical analysis showed no significant relationship between the overall implementation status and the challenges encountered, indicating that issues may arise independently of implementation quality. These findings underscore the need for more focused professional development, improved reporting structures, and enhanced stakeholder involvement to sustain and strengthen the program. The study concludes that although the anti-bullying initiative is operational, further strategic interventions are necessary to ensure its effectiveness and long-term impact.